Technological diversification and innovation performance - Thomas Bolli; Martin Wörter (ETH Zurich, KOF Swiss Economic Institute, 2013)
This paper analyzes the impact of technological diversity on innovation inputs and success using Swiss firm-level panel data. While we do not find any impact of diversity on R&D intensity, we confirm a positive impact of diversity on patent applications as suggested by the literature. However, since patent applications reflect an intermediate innovation input rather than output, we extend the analysis to the share of sales generated by new products. We find a significant negative effect of diversity on the sales share of new products. Hence, technologically more specialized firms have a lower propensity to patent and greater shares of new products. We find neither a direct nor indirect effect of diversity on the sales share generated by improved products. These results suggest that specialization pays-off through more drastic innovations that yield greater market success through a passing monopoly status.
Keywords: O3; 330; patent applications; innovative sales share; new products; improved products; technological diversity; Patent; Industrielle Forschung; Innovation; Technologiewahl; Schweiz